2016
DOI: 10.3390/ijms17111905
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Density Positive to Tryptase Correlate with Microvascular Density in both Primary Gastric Cancer Tissue and Loco-Regional Lymph Node Metastases from Patients That Have Undergone Radical Surgery

Abstract: Mast Cells (MCs) play a role in immune responses and more recently MCs have been involved in tumoral angiogenesis. In particular MCs can release tryptase, a potent in vivo and in vitro pro-angiogenic factor via proteinase-activated receptor-2 (PAR-2) activation and mitogen-activated protein kinase (MAPK) phosphorylation. MCs can release tryptase following c-Kit receptor activation. Nevertheless, no data are available concerning the relationship among MCs Density Positive to Tryptase (MCDPT) and Microvascular D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 65 publications
2
22
0
3
Order By: Relevance
“…To the best of our knowledge, no other study has been published regarding the concomitant assessment of both MCDPT and TAMs and neovascularization in TT and ANT from GC patients. We propose that the coupled MCDPT and TAMs could be considered as a surrogate biomarker of the degree of GC angiogenesis [ 50 , 63 , 64 , 65 ]. From a therapeutic point of view, the data obtained support a novel possibility to inhibit GC angiogenesis by targeting the coupled TAMs and MCDPTs by mean of several agents (e.g., trabectedin, peptide M2, PLX3397, STI571, AB1010).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no other study has been published regarding the concomitant assessment of both MCDPT and TAMs and neovascularization in TT and ANT from GC patients. We propose that the coupled MCDPT and TAMs could be considered as a surrogate biomarker of the degree of GC angiogenesis [ 50 , 63 , 64 , 65 ]. From a therapeutic point of view, the data obtained support a novel possibility to inhibit GC angiogenesis by targeting the coupled TAMs and MCDPTs by mean of several agents (e.g., trabectedin, peptide M2, PLX3397, STI571, AB1010).…”
Section: Discussionmentioning
confidence: 99%
“…[21] Tryptase-positive MCs have a role in angiogenesis in the primary tumor and in LNs of patients with metastatic GC. [22] Endometrial carcinoma An increased number of MCs were observed in different stages in which grade III showed the highest MC accumulation. Tryptase-positive MC accumulation was in correlation with angiogenesis and tumor progression.…”
Section: Breast Cancermentioning
confidence: 99%
“…Tryptase is stimulating proliferation of endothelial cells by activation of the proteinase-activated receptor-2 (PAR-2) [ 48 ] and VEGF is produced by this process [ 49 ]. Tryptase is mainly released by infiltrating mast cells and is thereby marking them as a potential target for the anti-angiogenic therapy in gastric cancer patients [ 50 ].…”
Section: Angiogenic Signaling and Pathwaysmentioning
confidence: 99%
“…As initially described, the role of tryptase releasing mast cells in gastric cancer angiogenesis has been recently investigated. A higher density of mast cells was shown to be associated with a higher general vascularized area [ 50 ] in primary tumors and lymph node metastasis from patients undergoing resection of gastric cancer. In what way this parameter is helpful to predict survival and response to anti-angiogenic therapy has to be shown by clinical trials in the future.…”
Section: Translational Data and Angiogenic Factors As Biomarkersmentioning
confidence: 99%